2017
DOI: 10.1038/ajg.2016.555
|View full text |Cite
|
Sign up to set email alerts
|

Inadequate Utilization of Diagnostic Colonoscopy Following Abnormal FIT Results in an Integrated Safety-Net System

Abstract: Despite access to colonoscopy and a shared electronic health record system, colonoscopy completion after an abnormal FIT is inadequate within this safety-net system. Inadequate follow-up is in part explained by inappropriate screening, but there is an absence of clear documentation and systematic workflow within both primary care and GI specialty care addressing abnormal FIT results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
99
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(116 citation statements)
references
References 46 publications
8
99
2
Order By: Relevance
“…These results confirm and extend prior work examining colonoscopy follow‐up after abnormal stool‐based screening . A retrospective study in 2016, also performed in a safety net setting, found that only half of individuals with a positive FIT completed their colonoscopy within a year .…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…These results confirm and extend prior work examining colonoscopy follow‐up after abnormal stool‐based screening . A retrospective study in 2016, also performed in a safety net setting, found that only half of individuals with a positive FIT completed their colonoscopy within a year .…”
Section: Discussionsupporting
confidence: 83%
“…Additional studies in similar settings have identified follow‐up colonoscopy rates between 42% and 68% . In these cohorts, barriers to colonoscopy completion included increasing age, Hispanic ethnicity, female sex, and high comorbidity . To our knowledge, our sample describing colonoscopy referral and completion rates includes the largest number of distinct FQHCs to date.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors reported that 89% of patients with an abnormal FIT result were referred for follow‐up colonoscopy within 6 months, but only 44% actually underwent diagnostic colonoscopy. This level of follow‐up is consistent with the poor CDE rates reported in cited Veterans Administration, safety net, and other FQHC‐based studies …”
supporting
confidence: 86%
“…This level of follow-up is consistent with the poor CDE rates reported in cited Veterans Administration, safety net, and other FQHC-based studies. [7][8][9][10] An important strength of this study is that a relatively large number of FQHCs in a defined geographic area participated in the study. Even though participating FQHCs represented only 40% of the 20 FQHCs targeted for inclusion, the surprisingly low level of CDE performance in this and other published reports are concerning, and they support the authors' call for a CDE to be defined as a quality metric in CRC screening.…”
mentioning
confidence: 99%